Root Growth and Yield Response of Rainfed Lowland Rice to Planting Method - Sharma, P.K.; De Datta, S.K.; Redulla, C.A. (Cambridge University Press, 1987)
Field experiments were conducted on two soils (clay loam and sandy loam) with varying texture and water table depth to study the effects of two planting methods (dry seeding and transplanting) on the root growth and grain yield of rainfed lowland rice. About 75% of the roots were found in the top 10 cm soil. Root length density at the flowering stage and grain yield in the sandy loam soil, with a water table deeper than 1.5 m, were less in dry-seeded than in transplanted rice, probably because of the greater moisture stress in dry-seeded rice between late tillering and harvest. In the clay loam soil, with the water table mostly at the soil surface, there was no difference in grain yield between dry-seeded and transplanted rice.